The liminal space between hope and grief: The phenomenon of uncertainty as experienced by people living with relapsing-remitting multiple sclerosis - Eva C. van Reenen; Inge A. M. van Nistelrooij; Leo H. Visser; Janet W. K. de Beukelaar; Stephan T. F. M. Frequin; Alistair R. Niemeijer (PLoS ONE, 2025)
Background People with the chronic disease Multiple Sclerosis are subjected to different degrees of profound uncertainty. Uncertainty has been linked to adverse psychological effects such as feelings of heightened vulnerability, avoidance of decision-making, fear, worry, anxiety disorders, and even depression. Research into Multiple Sclerosis has a predominant focus on the scientific, practical, and psychosocial issues of uncertainty. In comparison, existential uncertainty has been under-researched, even though it might pose a greater burden to those experiencing it. Objective To understand the lived experience of uncertainty for people living with relapsing-remitting Multiple Sclerosis. Methods This study followed a phenomenological research design, employing elements of both the Reflective Lifeworld Approach and Phenomenology of Practice. Seventeen people with a recent (<1 year) diagnosis of relapsing-remitting Multiple Sclerosis were included. In-depth interviews were conducted immediately after inclusion. Results The lived experience of uncertainty can be described as a stumbling motion across the liminal space between hope and grief while dealing with oscillating feelings of unrest concerning the body, self, and others. The following four constituents further illuminate the meaning of the phenomenon: Having to constantly (re)define unfamiliar and intangible bodily changes on one’s own; Unsteady navigating amidst a destabilization of the imagined life; Relating to others as a source of, mirror or buffer for uncertainty; Going through overwhelming fears and worries while clinging to one’s own logic. Conclusion Adding to existing qualitative and phenomenological research into MS and theories on uncertainty, this study portrays uncertainty as a multifaceted experience. The findings imply the need for a continuous attunement of healthcare practitioners to the expectations, fears, avoidance techniques, and other uniquely personal circumstances of people with Multiple Sclerosis.